(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
This study examines the social-religion relations of Muslims and Buddhists in Lombok. Second, to examine how Muslims and Buddhists carry out traditional values to strengthen interreligious communication and relations. Third, to examine the efforts made by local communities to overcome socio-religious conflicts with communication perspectives. The research method used is phenomenology. Methods collected are through in-depth interviews. This study uses an interfaith communication approach. This research is important because social-religious conflicts still occur here. The study results show that the relations between Muslim and Buddhist communities in West Lombok are experiencing a dynamic process. Conflicts in the name of religion are still challenging for a plural society amidst the flow of social media. Interfaith communication and dialogue are key in anticipating and resolving socio-religious conflicts. Verbal and non-verbal communication in each tradition that strengthens the relationship between Muslim and Buddhist communities is shown in the Gawe Rapah, Nimbung, and Ngejot traditions. The communication values that exist in this tradition include preaching, unity, deliberation, and collective consciousness.